Surveillance of Acute SARS-CoV-2 Infections in Elementary Schools and Daycare Facilities in Bavaria, Germany (09/2020–03/2021) - Kern, Anna; Kuhlmann, Pia H.; Matl, Stefan; Ege, Markus; Maison, Nicole; Eckert, Jana; von Both, Ulrich; Behrends, Uta; Anger, Melanie; Frühwald, Michael C.; Gerstlauer, Michael; Woelfle, Joachim; et al. (Frontiers in Pediatrics, 2022)
Introduction: Here we report our results of a multi-center, open cohort study (“COVID-Kids-Bavaria”) investigating the distribution of acute SARS-CoV-2 infections among children and staff in 99 daycare facilities and 48 elementary schools in Bavaria, Germany. Materials and Methods: Overall, 2568 children (1337 school children, 1231 preschool children) and 1288 adults (466 teachers, 822 daycare staff) consented to participate in the study and were randomly tested in three consecutive phases (September/October 2020, November/December 2020, March 2021). In total, 7062 throat swabs were analyzed for SARS-CoV-2 by commercial RT-PCR kits. Results: In phase I, only one daycare worker tested positive. In phase II, SARS-CoV-2 was detected in three daycare workers, two preschool children, and seven school children. In phase III, no sample tested positive. This corresponds to a positive test rate of 0.05% in phase I, 0.4% in phase II and 0% in phase III. Correlation of a positive PCR test result with the local-7-day incidence values showed a strong association of a 7-day-incidence of more than 100/100,000 as compared to less than 100/100,000 (OR=10.3 [1.5 – 438], p<0.005). After phase III, antibody testing was offered to 713 study participants in elementary schools. A seroprevalence rate of 7.7% (students) and 4.5% (teachers) was determined. Discussion: During the initial waves of the SARS-CoV-2 pandemic, the risk of a positive SARS-CoV-2 result correlated positively with the local 7-day incidence. Hence, the occurrence of SARS-CoV-2 infections were reflected in schools and daycare facilities. An increased risk of SARS-CoV-2 transmission in the setting of daycare and elementary schooling was unlikely.